The status of implementation of the CGIAR Principles on the Management of Intellectual Assets: a submission from CGIAR to the Eleventh Session of the Plant Treaty’s Governing Body - CGIAR Genebank Accelerator (2025)
This is the fourth report from CGIAR to the Governing Body of the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty) concerning the status of the implementation of the CGIAR Principles on the Management of Intellectual Assets (CGIAR IA Principles).